2017
DOI: 10.1155/2017/5246853
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial-Targeted Molecular Imaging in Cardiac Disease

Abstract: The present study aimed to discuss the role of mitochondrion in cardiac function and disease. The mitochondrion plays a fundamental role in cellular processes ranging from metabolism to apoptosis. The mitochondrial-targeted molecular imaging could potentially illustrate changes in global and regional cardiac dysfunction. The collective changes that occur in mitochondrial-targeted molecular imaging probes have been widely explored and developed. As probes currently used in the preclinical setting still have a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 92 publications
0
11
0
Order By: Relevance
“…MitoTimer enables the study of mitochondrial structure, redox state, and mitophagic disposal by fluorescence microscopy on fixed tissue 326,327 . Finally, multiple radioactive tracers are being developed to monitor mitochondrial functions in real time in the setting of CVD 26,328 . These molecules, some of which are already approved for use in humans (for different applications), might constitute preferential tools to study the links between mitochondrial dysfunction and multiple forms of CVD in patients.…”
Section: Obstacles In the Development Of Mtasmentioning
confidence: 99%
“…MitoTimer enables the study of mitochondrial structure, redox state, and mitophagic disposal by fluorescence microscopy on fixed tissue 326,327 . Finally, multiple radioactive tracers are being developed to monitor mitochondrial functions in real time in the setting of CVD 26,328 . These molecules, some of which are already approved for use in humans (for different applications), might constitute preferential tools to study the links between mitochondrial dysfunction and multiple forms of CVD in patients.…”
Section: Obstacles In the Development Of Mtasmentioning
confidence: 99%
“…By contrast, a relatively large number of imaging studies have been reported with mitochondria-tropic radioprobes, mainly for in vivo tumor detection. This included several lipophilic cations originally developed for myocardial perfusion SPECT imaging, such as the cardiac agent 99m Tc-MIBI ( 99m Tc-Sestamibi) or the 99m Tc-TMEOP complex introduced by our group [ 14 , 15 , 16 , 17 , 18 ]. Among the mitochondrial-targeting moieties, the most widely applied is triphenylphosphonium (TPP), which is a delocalized cationic lipid that readily penetrates through the mitochondrial membrane due to the highly negative mitochondrial membrane potential [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, G-MPI can show abnormal local myocardial perfusion, which can be used for early noninvasive evaluation of abnormal changes in mitochondrial function of cardiomyocytes [43][44][45].…”
Section: Discussionmentioning
confidence: 99%